2014
DOI: 10.1016/j.bandl.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Inflectional morphology in primary progressive aphasia: An elicited production study

Abstract: Inflectional morphology lies at the intersection of phonology, syntax and the lexicon, three language domains that are differentially impacted in the three main variants of primary progressive aphasia (PPA). To characterize spared and impaired aspects of inflectional morphology in PPA, we elicited inflectional morphemes in 48 individuals with PPA and 13 healthy age-matched controls. We varied the factors of regularity, frequency, word class, and lexicality, and used voxel-based morphometry to identify brain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 53 publications
0
17
0
6
Order By: Relevance
“…However, they have difficulties when operations of morphology are made less reliable by allomorphy and their performance follows a graded pattern. Studies on inflectional morphology in SD show that participants have difficulties producing the past tense of irregular verbs, especially those of low frequency Wilson et al, 2014; for a review, see Auclair-Ouellet, 2015). As in inflectional morphology, semantic cognition would play an important role in the representation of less predictable words and in encoding the links between these words and those that are formed with the same base.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they have difficulties when operations of morphology are made less reliable by allomorphy and their performance follows a graded pattern. Studies on inflectional morphology in SD show that participants have difficulties producing the past tense of irregular verbs, especially those of low frequency Wilson et al, 2014; for a review, see Auclair-Ouellet, 2015). As in inflectional morphology, semantic cognition would play an important role in the representation of less predictable words and in encoding the links between these words and those that are formed with the same base.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, words ending in /ksjᴐ̃/ could constitute an intermediate level of transparency or predictability that was not considered in the initial selection of items. Studies show that the performance of participants with SD is influenced by regularity and frequency or "typicality" of items Wilson et al, 2014). Therefore, it was possible to expect that SD participants would have intermediate performances for items ending in /ksjᴐ̃/, that is, less good than for transparent words, but better than for allomorphic verb-noun pairs that correspond to another pattern.…”
Section: Accuracymentioning
confidence: 99%
“…Agrammatic speech in nfvPPA is caused by a lack of verbs (Hillis et al, 2002), a relatively small proportion of grammatical sentences, impaired production of verb inflection, as well as a lack of complex embedded structures and simple verb-argument structures (Wilson et al, 2014).…”
Section: Sentence Productionmentioning
confidence: 99%
“…Over the years, studies have shown that this central impairment has several consequences, including difficulties in language domains that are not traditionally considered to rely heavily on semantic cognition, such as inflectional morphology (Benedet, Patterson, Gomez-Pastor, & Garcia de la Rocha, 2006;Cortese, Balota, Sergent-Marshall, Buckner, & Gold, 2006;Jefferies, Rogers, Hopper, & Lambon Ralph, 2010;Lambon Ralph et al, 2011;Meteyard & Patterson, 2009;Meteyard, Quain, & Patterson, 2014;Murray, Koenig, Antani, McCawley, & Grossman, 2007;Patterson, Lambon Ralph, Hodges, & McClelland, 2001;Patterson et al, 2006;Rochon, Kavé, Cupit, Jokel, & Winocur, 2004;Sajjadi, Patterson, Tomek, & Nestor, 2012;Wilson et al, 2014; for a review, see Auclair-Ouellet, 2015). Support for the presence of morpholog-ical difficulties in SD comes in large part from studies that target the production of inflected verbs in controlled contexts (i.e., carrier 1 Published in Brain and Language 155-156, 1-11, 2016 which should be used for any reference to this work phrases) (Benedet et al, 2006;Cortese et al, 2006;Jefferies et al, 2010;Patterson et al, 2001Patterson et al, , 2006Wilson et al, 2014). In these contexts, the performance of SD patients is characterised by difficulties to produce the past-tense of irregular verbs, especially those of low frequency, while the production of regular inflected verbs is largely preserved (Jefferies et al, 2010;Patterson et al, 2001Patterson et al, , 2006Wilson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Support for the presence of morpholog-ical difficulties in SD comes in large part from studies that target the production of inflected verbs in controlled contexts (i.e., carrier 1 Published in Brain and Language 155-156, 1-11, 2016 which should be used for any reference to this work phrases) (Benedet et al, 2006;Cortese et al, 2006;Jefferies et al, 2010;Patterson et al, 2001Patterson et al, , 2006Wilson et al, 2014). In these contexts, the performance of SD patients is characterised by difficulties to produce the past-tense of irregular verbs, especially those of low frequency, while the production of regular inflected verbs is largely preserved (Jefferies et al, 2010;Patterson et al, 2001Patterson et al, , 2006Wilson et al, 2014). A rTMS study with young partic-ipants without cognitive impairment also supported the involve-ment of ATL in irregular verb inflection (Holland & Lambon Ralph, 2010).…”
Section: Introductionmentioning
confidence: 99%